Development and characterisation of recycled carbon fibre based films/composites for thermoelectric applications - R. Jagadish, Priyanka (2019)
The increasing usage of carbon fibres in the aerospace, automotive and sports goods industries since the late 20th century has led to an end-of-life concern for the carbon fibre composites. An estimated 3000 tonnes of carbon fibre scrap are generated annually throughout the United States of America (USA) and Europe. The disposal of carbon fibre through incineration or landfill has been deemed infeasible and there have been environmental regulations that have imposed a ban on this material as it is non-biodegradable. For instance, in 1999, the European Union has enforced the Landfill Directive (1999/31/EC) that restricts the disposal of carbon fibre as a chemical waste. Therefore, there is a need for recycling these carbon composites that would not only save disposal cost, but more importantly, provides an avenue for reuse in a more sustainable manner. In the framework of reuse of recycled carbon fibre (RCF) and alternative product development to close the recycling loop of RCF, this research aims to develop RCF based thermoelectric films and composites. Electrodeposition method was used to synthesise n-type bismuth telluride (Bi2Te3) films on recycled carbon fibre (RCF) under different deposition conditions. Electrodeposition was studied using single parameter and multi-parameter optimisation. From the single parameter optimisation, it was observed that close to stoichiometric n-type Bi2Te3 fims have higher Seebeck coefficient (-12.99 μV/K). Multi-parameter optimisation was carried out using D-optimal model under response surface methodology (RSM) to design the experiment and optimise the following deposition parameters: deposition potential (V), deposition time (h), deposition temperature (°C) and electrolyte composition (molar concentration). The Seebeck coefficient of Bi2Te3 coated RCF using multi-parameter optimisation (-17.25 μV/K) was 33 % higher than the Seebeck coefficient obtained using single parameter optimisation (-12.99 μV/K). This research work also focused on the development of a low-cost effective RCF polymer thermoelectric composite. This study investigated the effect of the concentration of Bi2Te3 and Bi2S3 fillers respectively on the thermoelectric, morphology, structural and thermal stability of the RCF thermoelectric composites. The power factor of RCF thermoelectric composites was highest at 45 wt% of thermoelectric filler loading at 0.194 µWK-2m-1 and 0.094 µWK-2m-1 for RCF-Bi2Te3 and RCF-Bi2S3 respectively. In order to further improve the electrical conductivity and the subsequent thermoelectric properties of RCF composites, this study also investigated and studied the effect of varying concentration of multiwall carbon nanotubes (MWCNT) on the thermoelectric properties of RCF-Bi2Te3 and RCF-Bi2S3 composites. The optimum doping level of MWCNT for RCF-Bi2Te3 and RCF-Bi2S3 is 0.10 wt% and 0.15 wt% of MWCNTs, respectively. At optimum doping level, MWCNTs enhanced the power factors of RCF-Bi2Te3 and RCF-Bi2S3 composites by approximately 439 and 800%, respectively. The highest power factor obtained for MWCNT doped RCF-Bi2Te3 and RCF-Bi2S3 are 1.044 and 0.849 µWK-2m-1, respectively. Lastly, to enhance the crystallinity and electronic transport properties of the RCF composites, thermal annealing essentially a heat treatment that alters the physical and chemical properties of a semiconductor was studied. The optimum annealing temperature for Bi2Te3 and Bi2S3 particles within the RCF composites are 350 and 400 °C respectively. In addition to temperature, the optimum annealing time for both RCF-Bi2Te3 and RCF-Bi2S3 is 2 hours. At optimum annealing temperature and time, the power factor of RCF-Bi2Te3 and RCF-Bi2S3 composites are 7.836 and 2.551 µWK-2m-1 respectively. Both annealed RCF-Bi2Te3 and RCF-Bi2S3 composites depicted a 4000 and 2600% improvement in power factor as compared to the non-annealed counterparts.